Diagnosis Feline Panleukopenia Berdasar Total Leukosit dan Uji Feline Parvovirus-Antigen pada Kucing-Kucing Diare - Purnamaningsih, Hary; Indarjulianto, Soedarmanto; Yanuartono, Yanuartono; Nururrozi, Alfarisa; Widiyono, Irkham; Rahardjo, Slamet; Hartati, Sri; Rusmihayati, Rusmihayati (Jurnal Veteriner; Vol 23 No 1 (2022), 2022)
Feline panleukopenia (FPL) is one of the most common disease that causes diarrheal and leukopenia in cats. The purpose of this study was to diagnose FPL based on total leukocyte and detection of feline parvovirus antigen (FPV-Ag) in diarrhea cats. This study used blood samples and feces swabs from 21 cats that showed symptoms of diarrhea. Total leukocytes are calculated from blood samples and the presence of FPV antigens is detected from feces swabs using FPV-Ag-kit. The suitability of the FPL diagnosis based on leukopenia and a positive reaction to the FPV-Ag test was compared using the Cohen’s Kappa suitability test. The results showed that 14 out of 21 cats (66.7%) had leukopenia and 7 of 21 cats (33.3%) had normal total leukocytes. Results of FPV-Ag test showed that 11 of 21 cats (52%) were positive and 10 of 21 cats (48%) were negative. The both test has a good agreement with a 0.71 conformity value. Based on this study it was concluded that the diagnosis of FPL based on total leukocyte and FPV-Ag have a good agreement, so that both tests could be used as a basis for FPL diagnosis.